Study on mechanical properties and luminescence function of pouring energy-storage luminescent asphalt mixture - Jin, Wenliang; Song, Shenyou; Li, Pengfei; Shan, Jinhuan; Xing, Chengwei (Frontiers in Materials, 2025)
Energy-storage luminescent pavements can provide illumination in dark or low-light environments, aiding drivers and pedestrians in better recognizing road conditions and thereby reducing the occurrence of traffic accidents. The pouring energy-storage luminescent asphalt mixture (PELAM) proposed in this study comprises a porous asphalt mixture matrix and long-afterglow-epoxy resin grouting material filling the voids within it. The mechanical properties of the mixture were studied through dynamic modulus, phase angle, and repeated loading creep tests; the effects of different void ratios, immersion times, and weather conditions on the afterglow brightness of the specimens were tested to analyze the impact on luminescent function. The results show that the dynamic modulus of PELAM gradually increases with the decrease of the test temperature, the increase of the loading frequency and the increase of the void ratio. The Phase angle changes lack a clear pattern with temperature and frequency variations. The flow number and the micro-strain corresponding to the flow number gradually increase with the increase of the void ratio. The void ratio and short-term immersion have little influence on the afterglow effect of pouring energy-storage luminescent asphalt mixture, and 21 days of immersion slightly reduces the afterglow brightness; under the excitation of natural light, the afterglow duration can last for more than 6 hours. The mechanical properties and luminescent function of PELAM are suitable for pavement applications.